2005
DOI: 10.1270/jsbbs.55.253
|View full text |Cite
|
Sign up to set email alerts
|

Historic Role of the Wheat Variety Akakomugi in Southern and Central European Wheat Breeding Programs

Abstract: The old semidwarf, not very attractive, Japanese wheat variety Akakomugi was the source of the dwarfing gene Rht8 and photoperiodic insensitive gene PpD1 to many semidwarf wheat varieties in South and Central Europe in the 20 th century. Integrating the Rht8 and PpD1 genes in wheat varieties offered the best opportunities for reducing plant height, accelerating time of flowering, improving grain fill before the onset of dry summer conditions, enhancing spikelet fertility, and consequently increasing yields. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 3 publications
3
20
0
Order By: Relevance
“…Likewise, the genotypes grouped in the fourth cluster with predominant Croatian varieties represented descendants of Mara and Libellula, two Italian varieties that had a great impact on wheat breeding in former Yugoslavia. These cultivars were improved for the local climatic conditions and industry requirements (Borojevic and Borojevic 2005). Our findings confirmed that population structure and genotype relatedness assessed with molecular markers are consistent with genotype origin and available pedigree data.…”
Section: Discussionsupporting
confidence: 83%
“…Likewise, the genotypes grouped in the fourth cluster with predominant Croatian varieties represented descendants of Mara and Libellula, two Italian varieties that had a great impact on wheat breeding in former Yugoslavia. These cultivars were improved for the local climatic conditions and industry requirements (Borojevic and Borojevic 2005). Our findings confirmed that population structure and genotype relatedness assessed with molecular markers are consistent with genotype origin and available pedigree data.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that Ppd‐D1a originated in Asia. Haplotype I was detected in many Chinese landraces, such as ‘Mazhamai’, ‘Youzimai’, ‘Jiangdongmen’ and ‘Wangshuibai’ in the present study, and in Japanese landraces, such as ‘Akakomugi’ (Borojevic, 2005). These landraces were used widely as parents in Chinese and worldwide wheat‐breeding programs.…”
Section: Discussionsupporting
confidence: 61%
“…These results demonstrated that the grain yield potential of wheat has risen from 4.86 to 7.81 t ha − For example, the improvement of kernels per spike can be attributed in part to the effect of the dwarfing genes coming from Akakomugi and introduced in modern genotypes (Borojevic and Borojevic 2005a). These genes have been reported to modify morphogenetic patterns within spikes, which can result in more kernels per spike (Austin et al 1980, Donmez et al 2001, Mladenov et al 2007.…”
Section: Discussionmentioning
confidence: 94%
“…Bezostaja 1 came from very complex crosses in which one parent was Klein 33 from Argentina. Klein 33 came from a cross in which one parent was Ardito, of which one parent was Akakomugi (Borojevic and Borojevic 2005a). The pathway of the Rht8 gene (of the variety Akakomugi) was from Japan to Italy, from Italy to Argentina and from Argentina to Europe and the former Soviet Union.…”
Section: Grain Yieldmentioning
confidence: 99%